Rheumatic heart valve disease: navigating the challenges of an overlooked autoimmune disorder - Lupieri, Adrien; Jha, Prabhash K.; Nizet, Victor; Dutra, Walderez O.; Nunes, Maria Carmo P.; Levine, Robert A.; Aikawa, Elena (Frontiers in Cardiovascular Medicine, 2025)
Despite being a leading cause of morbidity and mortality among young people, affecting predominantly women, rheumatic heart disease (RHD) remains neglected and understudied. This autoimmune condition arises from a complex continuum that begins with repeated Group A Streptococcal (GAS) pharyngitis, leading to acute rheumatic fever (ARF) that eventually results in damage to the heart, mainly affecting the mitral valve. While RHD has been nearly eradicated in high-income countries, it continues to be a significant and active health issue in low- and middle-income countries. The resolution of this disease faces several challenges, including the difficulty of diagnosis and the lack of access to preventive measures in resource-poor communities. Addressing these issues will require a global health collaboration involving healthcare professionals, policymakers, and advocacy groups. However, over the past two decades, there has been a revival of scientific interest, fostering optimism for the future. Recent research has significantly advanced our understanding of RHD, shedding light on the immune-to-autoimmune transition, neoangiogenesis, and lymphangiogenesis processes. Additionally, perspectives of discoveries in biomarkers and the development of genetic, transcriptomic, and provide a solid foundation for further advancements in the field.